Diverse worldviews education and social inclusion: a comparison between Finnish and Australian approaches to build intercultural and interreligious understanding. Issue 4 (1st October 2020) - Lipiäinen, Tuuli; Halafoff, Anna; Mansouri, Fethi; Bouma, Gary
ABSTRACT: Ongoing global issues relating to the decline of the popularity of institutional religions, the rise of numbers of non-religious persons, and new models of spirituality in superdiverse societies have resulted in the need to reconceptualise religious diversity as worldviews diversity, and to critically examine increasing calls for the provision of worldviews education in schools. This paper first examines the key concepts of superdiversity and religious complexity in contemporary societies. It then presents an overview of scholarship pertaining to the concepts of worldviews and worldviews education. It next provides case studies of worldview/s education in Finland and Australia, drawing on data of recently completed qualitative and quantitative studies in the two countries. Finally, it concludes with a comparative analysis of the two contexts, and recommendations pertaining to worldviews education as a means of enhancing cross-cultural literacy, positive attitudes to religious diversity and thereby social inclusion.